Strong Firms Lobby, Weak Firms Bribe: A survey-based analysis of the demand for influence and corruption - Morten Bennedsen; Sven E. Feldmann; David Dreyer Lassen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2009)
We use survey responses by firms to examine the firm-level determinants and effects of political influence, their perception of corruption and prevalence of bribe paying. We find that: (a) measures of political influence and corruption/bribes are uncorrelated at the firm level; (b) firms that are larger, older, exporting, government-owned, are widely held and/or have fewer competitors, have more political influence, perceive corruption to be less of a problem and pay bribes less often; (c) influence increases sales and government subsidies and in general makes the firm have a more positive view on the government. In sum, we show that strong firms use their influence to bend laws and regulations, whereas weak firms pay bribes to mitigate the costs of government intervention.
Keywords: 330; Interessenpolitik; Korruption; Unternehmenserfolg; Welt